The Prevention of Electoral Violence: A Panacea for Achieving Credible Election in Nigeria - Nnajieto, Augustina Onyedikachi; Nnajieto, Charles Chibuzor (International Journal of Humanities, Education, and Social Sciences, 2024)
Electoral violence is a critical challenge to democratic processes in Nigeria, undermining the credibility and integrity of elections. This paper explores the underlying causes of electoral violence and proposes strategies for its prevention to achieve credible elections. Drawing on Social Identity Theory (SIT), the study highlights how group dynamics and social identities shape behaviour and contribute to conflict during elections. Factors such as political exclusion, economic disparities, and historical grievances are identified as primary drivers of violence. The paper argues for a multifaceted approach to prevention, including fostering inclusive political representation, promoting intergroup dialogue, challenging harmful social norms, and supporting electoral education. Additionally, the role of responsible media, institutional legitimacy, and nonviolent conflict resolution are emphasized. By addressing the root causes and implementing these strategies, Nigeria can enhance the credibility of its elections and ensure a stable and democratic political environment. The study underscores the importance of understanding social dynamics and adopting comprehensive measures to mitigate electoral violence effectively.